How is COVID-19 reshaping temporary and circular labour migration: Serbia and North Macedonia perspectives - Lukic, Vesna; Predojevic Despic, Jelena; Janeska, Verica; Lozanoska, Aleksandra (Forum geografic. Studii și cercetări de geografie și protecția mediului, 2021)
The COVID-19 pandemic has caused migrant workers worldwide to face numerous and specific challenges. This study aims to determine how the COVID-19 pandemic and its societal impact have influenced temporary and circular migrants from Serbia and North Macedonia. Semi-structured in-depth interviews were conducted with 50 participants to gain a deeper understanding of their challenges and migration practices. Temporary circular labour migration from Serbia and North Macedonia are most intensive towards EU countries, which are geographically close and well-connected by traffic, and with which migrants have well-established migration ties. The results show that after the outbreak of the pandemic, respondents faced termination of employment contracts, reduced working hours and earnings. Most of the respondents returned and only a few found formal employment in the country of origin. Job-related impacts of COVID-19 on respondents are determined by temporary residence, a form of employment and the employment sector. Temporary and circular migrant workers from Serbia and North Macedonia involved in the essential sectors in EU countries are less likely to be severely affected by the economic impact of the COVID-19 pandemic. The results suggest that temporary and circular migration schemes should be improved after the pandemic, in a way that is sustainable even in times of sudden changes. In that regard, in addition to considering the needs of the labour markets of countries of origin and destination, the needs and the rights of migrants, should be prioritized in common solutions.
Keywords: labour migration; temporary migrants; circular migrants; COVID-19; Western Balkans